Effect of low-volume blood withdrawal on hematological biomarkers - Bastien Krumm; Jonas Saugy; Francesco Botrè; Raphael Faiss (Bern Open Publishing, 2023)
Introduction The hematological module of the Athlete Biological Passport (ABP) consists of individual and longitudinal monitoring of hematological parameters biomarkers responsive to erythropoiesis alteration. Based on an adaptive Bayesian model, the ABP seeks to identify non-physiological variations that may correspond to different types of blood doping. In this context, the impact of a standard blood donation (500 ml) was evident on the ABP parameters, hence supporting the robustness of the model. However, there is only scarce evidence of single or multiple withdrawals of smaller volumes of blood, closer to a modern blood doping strategy. This study investigated the impact of low-volume blood withdrawal on hematological variables for anti-doping purposes. Methods Twelve healthy subjects (7 women and 5 men; 26 ±6 yrs, 170 ±7 cm; 65 ±7 kg) were recruited. After baseline measurement, 140 ml whole blood was withdrawn with subsequent measures of hematological parameters by flow cytometry (Sysmex XN-1000, Sysmex Corporation, Japan) for 3 weeks. Blood volumes (BV) and total hemoglobin mass (Hbmass) were determined by means of a validated CO-rebreathing method. Ferritin (FERR) concentration was additionally measured by chemifluminescence immunoassay technique. Individual profiles were generated using the official ABP adaptive model using the official software platform of the World Anti-Doping Agency (WADA). Mixed model repeated measures analyses were run for each parameter to determine whether changes in the dependent (hematological variables) variables differed over time (fixed factor). Results 43.2 ±8 g of hemoglobin was removed during the 140 ml blood withdrawal. A significant decrease in Hbmass (726 ±185 vs. 709 ±189 g; p = 0.007) and Red Blood Cell Volume (RBCV; 2190 ±521 vs. 2129 ±552 L; p = 0.028) was observed at D + 7 with a return to basal value at D + 14. No significant variations were observed for the primary and secondary variables of the ABP. No Atypical Passport Finding (ATPF) were generated in the individual ABP profiles. Conversely, FERR was significantly downregulated at D + 7 (95.8 ±76 vs. 87.1 ±76 μg/l; p = 0.018). Discussion/Conclusion While the ABP has demonstrated substantial advantages for traditional doping scenarios, our results challenge the indirect detection of low-volume blood withdrawals in a contemporary blood doping scenario. The impact of low-volume autologous blood transfusion on time trial performance has recently been demonstrated, supporting the need for novel biomarkers with extended detection windows. Hbmass could hence represent an additional marker to screen blood doping while technical issues for the use of CO-rebreathing remain. FERR as a marker of altered iron metabolism was there against shown to be sensitive and possibly suitable for outlining low-volume blood transfusion. The large inter-subject variability underlines the importance of individual longitudinal monitoring to provide sufficient sensitivity in the interpretation of hematological variations. Our study finally confirms that even low-volume blood withdrawals are associated with significant hematological changes while frequent blood samples and additional biomarkers are certainly required to better tackle blood doping strategies using such low-volume transfusions.